The Role of The Uterus in Poetry Rumah Rahim, Pada Pemilik Rahim, and Upacara by Oka Rusmini - Rizkiyatussalamiyah, Mudrikah; Muhshonatun Nisa; Pinkan Zahrah Ramadhani; Dian Hartati (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2024)
Women play a crucial role in society because they have wombs that give birth to future generations of humans. However, the birth of children in Bali is still influenced by customs based on the father's line. This research was conducted to reveal the forms of feminism in the poems